High‐Performance Transparent Broadband Microwave Absorbers. Issue 4 (17th December 2021) - Wang, Heyan; Zhang, Yilei; Ji, Chengang; Zhang, Cheng; Lu, Zhengang; Liu, Yunfei; Cao, Zhibo; Yuan, Jing; Tan, Jiubin; Guo, L. Jay
Abstract: The ability to absorb a broad frequency range of microwaves is essential for improving the performance of various electromagnetic interference shielding applications. However, the achievement of broadband microwave absorption with high optical transparency remains a long‐standing and unsolved challenge. Here, a simple and powerful method for high‐efficiency broadband microwave absorption is presented by introducing strongly overlapped multi‐cavity resonances, which is supported by multi‐layer structures comprising of alternating graphene/silica pairs and ultrathin silver films. A design guideline for achieving broadband absorption in multi‐layer structures is proposed and, more importantly, the complementary effect of different graphene layers on the microwave absorption mechanism is revealed for the first time, providing a new analytical perspective. Experiments show that the absorption efficiency of the proposed multi‐layer structures is near unity (≈100%) at resonant peaks with absorption bandwidths (≥50%) up to ≈30 GHz within the measured range of 32 GHz. In addition, the multi‐layer structures exhibit highly visible transmittance ranging from ≈85.8% to 68.0%. The proposed general theoretical framework and physical insights in combination with experimental demonstrations lay the foundation for designing a new type of transparent broadband microwave absorber. Abstract : A multi‐layered structure consisting of graphene/silica units and ultrathin Ag films for transparent broadband microwave absorbers is demonstrated. A design guideline for achieving broadband absorption in multi‐layer structures is proposed and, more importantly, the complementary effect of different graphene layers on the microwave absorption mechanism is revealed, providing a new analytical perspective.